Pancasila Values In Tradition On The Bali Hindu Community Reviewed From Bali Adat Law And Hindu's Law - Arinita Sandria (Institut Hindu Dharma Negeri Denpasar, 2018)
Adat law is an unwritten law that applies to a particular society. One of adat law that is still valid in Indonesia is Balinese Adat Law which is strongly influenced by Hindu religious law. Adat Law Society of Bali has many traditions related to various religious activities, one of which is ngayah. The development of the times influenced the existence of the ngayah tradition in the Balinese Hindu community. Many Balinese Hindus, especially those outside Bali, currently do not carry out ngayah. This will certainly have a negative impact on the continuation of the ngayah tradition. This is what prompted researchers to conduct research on cultivation in the Balinese Hindu community. The problems raised by researchers in this regard are: 1) How the implementation of Pancasila values contained in ngayah in the Balinese Hindu community; and 2) How is the application of sanctions for Balinese Hindus who do not implement ngayah in terms of Adat Law and Hindu LawThis research was carried out in a descriptive analytical way, which provides a careful description of the facts that are related to the research. This study uses a juridical empirical approach. This research was conducted in two stages, namely library research (library research) and field data. Data collection techniques in this study were conducted in two ways, namely doku men and interview studies Data analysis was performed using qualitative juridical analysis methods. The location of the study to obtain data in this writing is the library and institutions related to research. The conclusions that can be drawn are: 1) Ngayah as a tradition in the Balinese Hindu community is very full of the values of Pancasila; and 2) Application of sanctions for Balinese Hindus who do not carry out ngayah in terms of Adat Law and Religious Law in general are customary sanctions in the form of danda